A prática nos cursos de licenciatura: reestruturação curricular da formação inicial - Campos, Márcia Zendron de (2006)
This study aims at underscoring the pressing search of a new meaning for the concept of practice in the initial teaching licensing formation course. Such meaning should refer to the legislation regulating this universe, and point at both a curricular restructuring panorama and the reflexive teaching theories for teacher education; those, in turn, face the issue of how to meet the National Curricular Guidelines (Resolutions CNE/ CP 01 and 02/2002) in relation to 800 hours of practice for teaching licensing courses. With the objective of identifying how such practice has been carried out, I conducted descriptive, interpretive and qualitative research in which, through the analysis of the discourse from 14 teachers in 5 teaching licensing courses in a private university, I found out the existence of the predominance of teaching practice and internship. However, good initiatives of changing from the concept of supervised internship emphasizing technical rationality toward a concept of the field of knowledge generated from reflexive practice have been suggested. Those initiatives show the intention of updating the practice dimension in the curriculum. The latter is, nevertheless, made difficult due to a certain misunderstanding in relation to both the nature of such practice as a curricular component and the way of using it, as inferred from the discourses analyzed in this study. From this realization, proposals and examples of how to apply this practice as a curricular component are presented in this study. It is also concluded that the articulation of theory and practice as the curricular core is not carried out, except in some isolated disciplines. Facing this situation, it may be said that the panorama does not favor the professional development underscoring the role of the teacher as someone active, critical, creative and compromised with the educational goals in Basic Education, away from the perspective of teacher professionalization